Metastatin as a Marker for Hyperandrogenemia in Iraqi Women with Polycystic Ovary Syndrome - Manal Madany Abdalqader; Shatha Sami Hussein (Hindawi Limited, 2020)
Objective. Kisspeptin 1 might reflect increased androgen level in polycystic ovarian syndrome instead of other markers. Study Design. A case control study was performed in Al-Yarmouk Teaching Hospital from 1st of July 2016 to 1st of July 2017; it involved 87 women divided into two groups: 44 women diagnosed as PCOS, 22 women with BMI ≥ 25 kg/m2 and 22 women with BMI < 25 kg/m2, and another 43 women without PCOS, 22 women with BMI ≥ 25 kg/m2 and 21 women with BMI < 25 kg/m2. Hormonal, metabolic profiles, and hirsutism scores, as well as serum kisspeptin level, were assessed by using Human Kisspeptin 1(KISS-1) ELISA Kit. The blood samples between days 2 and 5 of menstrual cycle were drawn by an disposable sterile syringe and collected in EDTA containing tubes (as anticoagulant), and the hormonal profile was measured using a biotech ELISA reader. Result. Serum level of kisspeptin was significantly higher in PCOS compared to control (322.4 vs. 235.3 ng/L, respectively). There was no significant difference in age, BMI, and parity between control and PCOS; the frequency of hirsutism, acne, elevated LH, and increased free testosterone (fTT) were significantly higher in PCOS compared to control. Kisspeptin shows a direct significant correlation with hirsutism and fTT (r = 0.648, 0.238, respectively). In ROC analysis, kisspeptin had AUC (95% CI) = 0.874 (0.785-0.935) for predicting PCOS. Conclusion. Kisspeptin levels might be used as a marker for hyperandrogenemia in polycystic ovarian syndrome.